Budd Chiari syndrome secondary to antiphospholipid syndrome and systemic lupus erythematosus in an adolescent: a case report - Atamari-Anahui, Noé (2022)
Budd-Chiari syndrome is caused by an obstruction of blood flow to the liver. Published cases of the antiphospholipid syndrome associated with BCS are limited in the pediatric population. We report a 15-year-old adolescent who presented with fever, ascites, and hepatosplenomegaly. Hepatic Doppler ultrasound revealed no flow in the right and middle hepatic veins and in the inferior vena cava. Abdominal tomography revealed extensive thrombosis of the inferior vena cava. During hospitalization, she was diagnosed with antiphospholipid syndrome and systemic lupus erythematosus. She was given treatment with unfractionated heparin, low molecular weight heparin, and anticoagulants. Budd-Chiari syndrome secondary to the antiphospholipid syndrome is a life-threatening disease. Timely diagnosis and treatment improve the quality of life of the patient.